Comunicação cooperativa usando retransmissão parcial codificada, HARQ tipo-I e códigos LDPC - Brante, Glauber Gomes de Oliveira (2010)
In this master thesis we present a novel HARQ scheme for cooperative communication systems, called Coded Partial Retransmission (CPR). The method is based on the retransmission of only a fraction of the original codeword by the cooperating nodes, applying an appropriate power allocation. Numerical results using LDPC codes and Type-I HARQ with Chase Combining show that CPR outperforms regular cooperative HARQ techniques considering both AAF and SDF protocols. Additionally, we show that the CPR throughput, using a single relay, may be considerably larger than the throughput of some regular cooperative HARQ schemes using multiple relays.